ANALISIS KINERJA USAHA PEDAGANG LAPAK SELAMA MASA PANDEMI COVID-19 DI KOTA KENDARI - Waode Nurmaya; Sabir Ahmad; Rosnawintang Rosnawintang (Universitas Halu Oleo, 2022)
This study aims to determine and analyze the performance of small and medium businesses during the COVID-19 pandemic in Kendari City. The type of data used is qualitative data, namely primary and secondary data sourced from BPS and primary data processed by the researchers themselves. Data collection methods used are interviews, questionnaires, observation, and documentation. The analytical tool used is Descriptive Statistical Analysis using tables, averages and percentages. The results of the study show that the performance of Small and Medium Enterprises (SMEs) in Kendari City has decreased since the Covid-19 pandemic occurred. The decline was due to a lack of consumers buying products marketed by SMEs due to government policies that restrict people from interacting outside the home, causing the sales volume of SMEs to decrease greatly and resulting in greatly reduced income (profits) SMEs also still do not utilize information technology in helping SMEs in marketing products.